The lean six sigma training set - Ptacek, Rob; Motwani, Jaideep Gridhari (MCS Media, 2011)
"The Lean Six Sigma Training Set is your complete set of materials for conducting training on the tools and concepts of Lean and Six Sigma. With over 300+ PowerPoint slides, each tool is thoroughly explained with examples from a wide range of industries as well as administrative and desktop processes. Use this Training Set to customize and add/remove examples and photos as you deem appropriate. No training program that is purchased can be exactly what you want, therefore, it is expected this set be customized. Included in this Training Set are the following items: 1 - Facilitator’s Guide that has the detailed Instructor Notes referencing The Lean Six Sigma Pocket Guide XL and Pursuing Perfect Service books 4 - The Lean Six Sigma Pocket Guide XLs 1 - CD that contains the PowerPoint presentation, simulation, Jeopardy Game, and exercises"--Resumé vydavatele
Keywords: Six Sigma (metoda); management jakosti; procesní management; Six Sigma (Quality control standard); quality control; process management; CD-ROM; učební texty; educational texts